Health, fun and ontonorms: museums promoting health and physical activity. (4th May 2021) - Bønnelycke, Julie; Grabowski, Dan; Christensen, Julie Hellesøe; Bentsen, Peter; Jespersen, Astrid Pernille
ABSTRACT: Recent years have seen an increase in health-related activities and exhibitions, as a rising number of museums are addressing global public health challenges. Museums have been identified as promising actors for the promotion of health and the communication of health knowledge, as they have the ability to provide meaningful and relevant learning experiences. However, we argue that the turn to health in museums risks the enactment of knowledge deficits in the audiences, with museums acting as health authorities, providing 'correct answers' and prescriptions for action, rather than being fora for the discussion of health as a socio-scientific issue and everyday experience. Employing the concepts of logic of care and onto norms from Annemarie Mol, and based on qualitative studies of three cases of health-promoting exhibitions, we discuss the implications of health promotion situated in a museum setting, and how museums can work to address health in a situated and careful manner.